PENERAPAN METODE BERCERITA DALAM KEMAMPUAN MEMBACA ANAK USIA DINI 5-6 TAHUN DI TK KARYA MANDIRI 2 KRAMATWATU - Uhtafiah, Uhtafiah; Sari, Novita; Nur, Maulida (Jurnal Anak Bangsa, 2025)
Early reading is one of the preparations for kindergarten children to be able to read simple words, know the spelling and meaning of the words. Early reading can have a positive impact on children's language development for educational levels. Early reading is a reading activity that is taught in a programmed manner to preschool children. This program focuses on words that are complete and meaningful in the child's personal context. One method that can stimulate early childhood to develop their language is through the storytelling method. The storytelling method is a way to convey or present learning materials orally in the form of stories from teachers to children. In educational units, storytelling is one method to improve early language skills that can develop several physical and psychological aspects of early childhood according to their developmental stages. The purpose of writing this research is to determine the application of the storytelling method in the reading skills of early childhood children aged 5-6 years at Karya Mandiri 2 Kramatwatu Kindergarten. This type of research uses a qualitative method with a case study approach. Data collection techniques are carried out by means of observation, interviews and documentation. The results of this study indicate the application of the early childhood storytelling method to reading skills. The storytelling method is very helpful for early childhood to develop their language skills. In addition, the storytelling method can also develop children's imagination, making children braver and more confident.